Did the Global Financial Crisis Break the U.S. Phillips Curve? - Laseen, Stefan; Taheri Sanjani, Marzie (Washington, D.C. : International Monetary Fund, 2016)
Inflation dynamics, as well as its interaction with unemployment, have been puzzling since the Global Financial Crisis (GFC). In this empirical paper, we use multivariate, possibly time-varying, time-series models and show that changes in shocks are a more salient feature of the data than changes in coefficients. Hence, the GFC did not break the Phillips curve. By estimating variations of a regime-switching model, we show that allowing for regime switching solely in coefficients of the policy rule would maximize the fit. Additionally, using a data-rich reduced-form model we compute conditional forecast scenarios. We show that financial and external variables have the highest forecasting power for inflation and unemployment, post-GFC.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet